Star Over Bethlehem - Mallowan, Agatha Christie (London Collins, 1965)
The stories and poems in this little book celebrate Christmas. In them, the most famous living writer of detective stories is not concerned with the darker aspects of human behaviour, but with the joys of creation and its riddles. Some of her stories are set during the past thousand years, others belong to the present and the near future; each one leaves the impress of its wisdom, pathos or humour.
Keywords: Literature